Health policy versus kava (Piper methysticum): Anxiolytic efficacy may be instrumental in restoring the reputation of a major South Pacific crop. (25th March 2021) - Thomsen, Michael; Schmidt, Mathias
Abstract: Ethnopharmacological relevance: Kava ( Piper methysticum G. Forst. f.) is by far the most important plant used in the islands of Melanesia, Polynesia and Micronesia for its relaxing effects. Kava drinking is a pillar of South Pacific societies and is also the foundation of their economies. Preparations of kava extract as herbal medicinal drugs were banned in Germany in 2002 and again in 2019, with dramatic consequences for the South Pacific economies. In 2002, the major regulatory argument for the ban of kava was safety issues. In 2019, the assessment report of the European Medicines Agency's Herbal Medicinal Product Committee (HMPC) justified a negative benefit-to-risk ratio by a supposed lack of efficacy of ethanolic extracts for an indication of which kava extract preparations never had an approval. In this HMPC report the efficacy in the approved indications 'nervous anxiety, tension and restlessness' was attributed to the extract branded as 'WS 1490', which was assumed to have been prepared with acetone as an extraction solvent. In addition to this change of indication and the attribution of efficacy to acetone kava extract alone, the German health authorities and the HMPC still refuse to discuss quality issues as a likely factor impacting drug safety. The first case reports of liver toxicity were observed with an acetone extract in a timely relationship with the introduction of 'two-day kava' instead of 'noble kava' as used in ethanolic kava extracts. Aim of the study: The correlation between clinical benefits and the type of extract preparation was examined. Methods: In order to identify the types of kava material and extracts used in clinical trials, the respective publications were compared with regulatory databases and protocols of a German regulatory advisory board. Results and conclusions: The comparison reveals inconsistencies in the regulatory decisions. In all studies with WS 1490, the evidence points to the use of an ethanolic extract. The efficacy of kava extract for the approved indication was clearly demonstrated. The HMPC report and the recent renewed German regulatory ban of kava therefore require major revision, which should include the impact of the use of "two-day kava" on drug safety. Such a revision could contribute to restoring the reputation of "noble kava" on the international markets. Graphical abstract: Image 1 Highlights: Kava extract preparations are efficacious in nervous anxiety, tension and restlessness. The HMPC's assumption of generalized anxiety as the indication of kava is unfounded. The attribution of the clinical evidence to acetone extracts must be questioned. There is evidence that the branded extract "WS 1490" was prepared with ethanol. There are inconsistencies in the procedures, which led to the prohibition of kava. The substitution of noble with two-day kava has never been examined.